2017
DOI: 10.1016/j.vetpar.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniosis in naturally infected dogs in Paraná, Brazil, and the epidemiological implications of Leishmania (Viannia) braziliensis detection in internal organs and intact skin

Abstract: Environmental changes have occurred over the years, altering the eco-epidemiological pattern of leishmaniosis in the State of Paraná, Brazil, involving the pillars of the cycle (parasite, vectors, reservoir, and environment) and their interaction. Much has been discussed about the dog's role as a reservoir of the Leishmania (Viannia) braziliensis Vianna, 1911 transmission cycle. However, this question remains unanswered. The purpose of this study was to investigate, using parasitological and molecular methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
1
11
0
3
Order By: Relevance
“…However, the majority of these studies lack documentation that L . braziliensis was the causal agent of the infection [8, 3139]. Here, evaluating 61 dogs with ulcerated lesions, evidence of leishmaniasis infection was observed in 89%, and 67% of the animals had detection of DNA of L .…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these studies lack documentation that L . braziliensis was the causal agent of the infection [8, 3139]. Here, evaluating 61 dogs with ulcerated lesions, evidence of leishmaniasis infection was observed in 89%, and 67% of the animals had detection of DNA of L .…”
Section: Discussionmentioning
confidence: 99%
“…The same authors suggested that dogs play an important role in the peridomestic transmission of ACL to human beings as confirmed by Membrive et al (2012). Recently, evidences that dogs can possibly act as reservoir of L. (V.) braziliensis were reported in study performed in an endemic rural area in northern Paraná State -Brazil (Marquez et al, 2017), however, no correlation or association between human and canine seroprevalences was recorded in another study in Londrina -PR (Benitez et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…Several nuclear and mitochondrial DNA markers (cytochrome b, COII, gp63, 18S-rRNA, mini-exon, HSP-70, and ribosomal internal transcribed spacer regions (ITS-rDNA)) as well as different molecular techniques such as polymerase chain reaction (PCR) [9], multilocus sequence typing (MLST) [10], multilocus enzyme electrophoresis (MLEE) [5,11], random amplified polymorphism (RAPD) [12], amplified fragment length polymorphisms (AFLP) [13] and microsatellites [14], have been used to evaluate the inter and intraspecific genetic variability of different Leishmania species (L. tropica, L. major, L. donovani, L. braziliensis, L. peruviana, L. guyanensis, and L. panamensis) [13][14][15][16][17][18][19]. However, the identification of such genetic variants across the whole genome has become possible only with the arrival of DNA-seq.…”
Section: Introductionmentioning
confidence: 99%